Students Emotional State during Recreational Skiing - Nikonovs, Intars; Grants, Juris; Kravalis, Ivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the research was to evaluate emotional state before, after and in the next day after the ski hiking. The distance was 24 km and lasted 8 hours. To assess the ski hiker’s emotions the following 3 tests were conducted – before the ski hike, after the ski hike and 16 hours after the hike. Emotional state was set by the two different methods. One included assessing participant’s dynamic of emotional state with subjective measurement using questioner, but other using subjective method by analyzing person’s facial expressions. The results showed improved emotional state in both ways. Although, using objective method, improved positive emotions were more in the next day of the ski hike.